Tandem reactions for sp3-rich scaffold synthesis - Bawazeer, Wafa Abubaker S. (2016)
Several novel methodologies were explored with the general purpose of rapid access to molecular complexity and sp3-rich scaffolds. A number of novel scaffolds were successfully synthesised, utilising two-directional synthesis and tandem reactions. The chemistries applied have been demonstrated to be capable of readily fabricating many novel and interesting diverse molecular scaffolds. Indeed, the azaspirocyclic cores found in halichlorine and pinnaic acid were synthesised using this approach starting with ethyl formate. More diverse scaffolds were generated from simple symmetrical linear molecules derived from ethyl formate, utilising the nitrone produced in situ by the treatment of the central ketone with either hydroxylamine hydrochloride or amino acids. These afforded number novel skeletons [A-C], which are expected to have interesting biological activity. In addition, they are conceivably useful skeletons in the synthesis of natural products, or in drug synthesis due to its high saturation (high Fsp3) characters. Using the tandem reactions, we have also managed to develop a rapid synthetic route to an sp3 -rich chemical scaffold [F] derived from novel isoxazolidine scaffold [E]. This project has been published with a contribution of other group member. We were interested to synthesise of some natural products. We tried to explore the possibility of developing an enantioselective synthesis approach to the key intermediate in the synthesis of hippodamine [H], few attempts toward the synthesis of the marine alkaloids phakellin [I]. Several novel applications of chiral sulfinimines were explored. Initially some preliminary results toward the synthesis of piperidine dione [I] were recorded. Successful attempts of tert-butyl sulfinimines with dianion tert-butyl-acetoacetate afforded a range of cyclic compound piperdine dione [J] in a good yield.